3DLC: A Comprehensive Model for Personal Health Records Supporting New Types of Medical Applications. Issue 3 (2nd September 2011) - Helmer, Axel; Lipprandt, Myriam; Frenken, Thomas; Eichelberg, Marco; Hein, Andreas
Abstract : Motivated by the demographic change, many new medical applications are installed in the user's home environment. These applications make use of ambient sensors, enabling new forms of medical care. Personal Health Records (PHRs) are an instrument for the storage, presentation and communication of health related data provided by these applications. But there are still open issues regarding the cooperation between PHRs and the new applications. On the basis of two medical application scenarios, we developed a new model which defines the appropriate level of abstraction of data generated by medical applications to be stored inside the PHR. The model also determines which part of these data is relevant for the clinical decision making process, and how these data should be communicated to physicians. This paper describes the 3DLC model, which uses three dimensions (clinical decision, frequency and context dependence) to determine the type of the data. We further introduce a prototype PHR system that is able to fulfil the requirements of our scenarios.